2021
DOI: 10.1021/acssensors.1c01718
|View full text |Cite
|
Sign up to set email alerts
|

A Valve-Enabled Sample Preparation Device with Isothermal Amplification for Multiplexed Virus Detection at the Point-of-Care

Abstract: Early and accurate detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza viruses at the point-of-care is crucial for reducing disease transmission during the current pandemic and future flu seasons. To prepare for potential cocirculation of these two viruses, we report a valve-enabled, paper-based sample preparation device integrated with isothermal amplification for their simultaneous detection. The device incorporates (1) virus lysis and RNA enrichment, enabled by ball-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Hence, 10 min was the most appropriate reaction time to monitor SARS-CoV-2 quantitatively in gel system. This is an ultrafast amplification for the SARS-CoV-2 testing compared with other methods ( Broughton et al, 2020 , Juang et al, 2021 , Manzanas et al, 2021 , Zhu et al, 2020 ). Similarly, we selected different concentrations of reagents (total Mg 2+ , loop primer, and reverse transcriptase) and temperature gradients to investigate the highest single-molecule amplification efficiency within 10 min (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, 10 min was the most appropriate reaction time to monitor SARS-CoV-2 quantitatively in gel system. This is an ultrafast amplification for the SARS-CoV-2 testing compared with other methods ( Broughton et al, 2020 , Juang et al, 2021 , Manzanas et al, 2021 , Zhu et al, 2020 ). Similarly, we selected different concentrations of reagents (total Mg 2+ , loop primer, and reverse transcriptase) and temperature gradients to investigate the highest single-molecule amplification efficiency within 10 min (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a long detection time of SARS-CoV-2 is a limitation for rapid acquisition of screening results. As for illustration, virus lysis, RNA purification, inhibitor removal, RNA reverse transcription, and cDNA amplification are vital steps for SARS-CoV-2 nucleic acid detection ( Juang et al, 2021 , Manzanas et al, 2021 , Zhang et al, 2021 , Zhu et al, 2022 ). Usually, 30-60 minutes are required for RNA reverse transcription and cDNA amplification process.…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric detection for SARS-CoV-2 and H1N1 virus was achieved with LODs of 2 and 6 genomes per reaction, respectively. Furthermore, this device can detect virus particles from clinical and environmental samples [ 60 ]. Bokelmann et al [ 61 ] presented the Cap-iLAMP acronym for capturing and an improved loop-mediated isothermal amplification method for smartphone-based colorimetric detection of SARS-CoV-2 from gargle lavage samples ( Figure 2 E).…”
Section: Lamp Detection Methodsmentioning
confidence: 99%
“…( E ) Workflow of Cap-iLAMP. Reproduced with permission from references [ 49 , 51 , 53 , 60 , 61 ]. Copyright 2021 and 2022 Springer Nature, 2021 American Chemical Society, 2021 MDPI.…”
Section: Lamp Detection Methodsmentioning
confidence: 99%
“…Detection was then detached from the whole device and incubated in a smart coffee mug for amplification. Another study performed by Manzanas et al from the same research group showed that the ball-based valve-enabled sample preparation device is adaptable to nasal swabs for duplex SARS-CoV2 and influenza A H1N1 detections 105 and has now further integrated the technology for to airborne virus detection. 106 To date, CRISPR-based diagnostics are mostly performed in tube in liquid phase followed by LFIA readout, [107][108][109][110][111] however, Yin et al 96 recently developed a multiplexed CRISPR-RPA assay of SARS-CoV-2 on a paper platform to improve suitability at the POC.…”
Section: Progression Towards User-actuated Sample-to-answer Devicesmentioning
confidence: 99%